Does gratitude enhance prosociality: a meta-analytic review - Ma, Lawrence; Tunney, Richard J.; Ferguson, Eamonn (American Psychological Association, 2017)
Theoretical models suggest that gratitude is linked to increased prosociality. To date, however, there is a lack of a comprehensive quantitative synthesis of results to support this claim. In this review we aimed to 1) examine the overall strength of the association between gratitude and prosociality, and 2) to identify the theoretical and methodological variables that moderate this link. We identified 252 effect sizes from 91 studies across 65 papers— (Total N = 18,342 participants). The present meta-analysis revealed a statistically significant, and moderate positive correlation between gratitude and prosociality (r = 0.374). This association was significantly larger among studies that assessed reciprocal outcomes relative to non-reciprocal outcomes, and in particular among studies that examined direct—compared to indirect—reciprocity. Studies that examined gratitude as an affective state reported significantly larger effect size studies assessing gratitude as a trait. Studies that examined benefit-triggered gratitude (in response to other’s kindness) had a stronger effect that generalized gratitude that focuses on the appreciation of what is valued and cherished in life. Finally, studies that manipulated gratitude in-vivo (e.g., economic games) had larger effect sizes compared to those based on recalled incidents when the person felt grateful. We describe the theoretical and practical significance of the results.